Teacher Work Productivity in a Leadership Perspective: The Role of Instructional Leadership of School Principals, Employee Engagement and Power Motivation - Atria Liyustari; Anisah; Ahmad Sabandi; Novriyanti Achyar (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Teacher work productivity is an important determinant of educational quality, yet it is influenced by both organizational conditions and teachers’ psychological characteristics. This study aims to examine the effects of principal instructional leadership and employee engagement on teacher work productivity and to investigate the mediating role of teachers’ power motivation. A quantitative approach with a correlational ex post facto design was employed. The population comprised 2,003 civil servant teachers from 45 public junior secondary schools in Padang, Indonesia. Using multistage sampling and the Cochran formula, 416 teachers from 28 schools were selected as respondents. Data were collected through a five-point Likert-scale questionnaire measuring instructional leadership, employee engagement, power motivation, and teacher work productivity. Data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS through measurement- and structural-model evaluation and bootstrapping at a 5% significance level. The findings indicate positive relationships between instructional leadership, employee engagement, power motivation, and teacher work productivity. Instructional leadership and employee engagement also positively contributed to teachers’ power motivation, while power motivation contributed positively to productivity. Furthermore, power motivation mediated the relationships between instructional leadership and teacher productivity and between employee engagement and teacher productivity. The model explained 52.1% of the variance in power motivation and 60.7% of the variance in teacher work productivity. These findings highlight the importance of integrating instructional leadership, employee engagement, and constructive power motivation to strengthen sustainable teacher productivity and school improvement.